Peningkatan Kandungan Protein Kulit Umbi Ubi Kayu Melalui Proses Fermentasi - Nurhayani H. Muhiddin; Nuryati Juli; I Nyoman P. Aryantha (Jurnal Matematika & Sains, 2001)
The objective of this research was to increase the protein content of cassava peel caused by microbial growth and its fermentation process on it, and to determine the population and diversity of the microbes in âragi tapeâ as inoculum. The method used in this process was solid substrate fermentation of cassava peel with ragi tape as inoculum. Prior to fermentation process, cassava peel as a substrate was treated with 1. fresh, 2. steaming, 3. additional of urea and rice brand and 4. additional of NPK and vitamine B1. The results showed that protein content in fermented fresh cassava peel increased from 3.41 % to 5.53 % after 8 days incubation with 3.09 g/kg inoculum, in fermented steamed cassava peel was 8.03 % after 5 days fermentation in fermented cassava peel with additional of urea and rice brand was 8.88 % after 4 days fermentation while 4.69 % in fermented cassava peel with additional of NPK and B1 vitamine after 5 days fermentation.